A Review on the Use of Gamification in Human Resource Management - Jessy Sini Dass, Arun Antony Chully (International Journal of Advanced Science and Technology, 2020)
Gamification as an effective method has pervaded into various aspects of human engagement in organizations. This review paper summarizes the existing literature on Gamification and traces the recent progress of gamification in the field of Human Resource Management. The paper reviews chronologically how gamification has evolved over a period of time in enhancing engagement and learning in the corporate sector with special emphasis on the domain of HRM. Three areas of special focus of this study are the impact of gamification on recruitment, training, employee performance, and engagement.  It explores further on how game mechanics and game designs in gamification represent a promising tool for HR professionals in the future.